2009
DOI: 10.4304/jmm.4.6.435-441
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison and Application of Corner Detection Algorithms

Abstract: Corners in images represent a lot of important information. Extracting corners accurately is significant to image processing, which can reduce much of the calculations. In this paper, two widely used corner detection algorithms, SUSAN and Harris corner detection algorithms which are both based on intensity, were compared in stability, noise immunity and complexity quantificationally via stability factor η, anti-noise factor ρ and the runtime of each algorithm. It concluded that Harris corner detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…Chen et al [11] performed a comparison of Harris-Stephens-Plessey and SUSAN based on metrics such as stability, noise immunity, complexity and run-time. They concluded that Harris-Stephens-Plessey was superior to SUSAN on the whole.…”
Section: Experimental Evaluation Of Four Feature Detection Methods Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [11] performed a comparison of Harris-Stephens-Plessey and SUSAN based on metrics such as stability, noise immunity, complexity and run-time. They concluded that Harris-Stephens-Plessey was superior to SUSAN on the whole.…”
Section: Experimental Evaluation Of Four Feature Detection Methods Fomentioning
confidence: 99%
“…In this paper we perform an experimental evaluation of four feature detection methods widely used in the implementation of many target detection approaches reported in the literature [8] [9] [10] [11]: Features from Accelerated Segment Test (FAST) [12], Harris-Stephens-Plessey feature detection [13], Shi and Tomasi -Minimum Eigenvalue feature detection [14], Smallest Univalue Segment Assimilating Nucleus (SUSAN) feature detection [15]. The four methods are evaluated based on their ability to detect features corresponding to close range and distant targets in frames from three video streams recorded in October 2010 using two aircrafts and a tri-focal video recording system [16].…”
Section: Introductionmentioning
confidence: 99%
“…If the absolute gradient values in two directions are both great, then judge the pixel as a corner. Harris corner detector is defined as follows [11]:…”
Section: Leukocyte Detection Systemmentioning
confidence: 99%
“…Harris corner detector is one of the most well-known corner detectors and is based on measuring the corner strength. Comparison between Harris corner detector and other corner detectors like SUSAN shows the superiority of Harris corner detector in the case of stability and complexity (running time) [25]. Therefore, Harris corner detector is used for feature extraction.…”
Section: Corner Detection Algorithmsmentioning
confidence: 99%